2019
DOI: 10.1056/nejmoa1815671
|View full text |Cite|
|
Sign up to set email alerts
|

Darolutamide in Nonmetastatic, Castration-Resistant Prostate Cancer

Abstract: BACKGROUNDDarolutamide is a structurally unique androgen-receptor antagonist that is under development for the treatment of prostate cancer. We evaluated the efficacy of darolutamide for delaying metastasis and death in men with nonmetastatic, castrationresistant prostate cancer. METHODSWe conducted a randomized, double-blind, placebo-controlled, phase 3 trial involving men with nonmetastatic, castration-resistant prostate cancer and a prostate-specific antigen doubling time of 10 months or less. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
586
2
45

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 699 publications
(685 citation statements)
references
References 24 publications
7
586
2
45
Order By: Relevance
“…Similar rates of CNS AEs were reported in a previous study by Pilon et al 14 using real-world data from patients with advanced PC, including those with metastatic disease. We found that patients initiating 10,11,29 . In addition to providing information about the incidence of AEs in the nmPC patient population, our results showed that prior AEs and a CCI score of 1 (vs 0) in the baseline period increased the likelihood of experiencing an AE after initiating enzalutamide, bicalutamide, or abiraterone therapy, consistent with what has previously been reported among patients with advanced PC 14 .…”
Section: Discussionmentioning
confidence: 73%
“…Similar rates of CNS AEs were reported in a previous study by Pilon et al 14 using real-world data from patients with advanced PC, including those with metastatic disease. We found that patients initiating 10,11,29 . In addition to providing information about the incidence of AEs in the nmPC patient population, our results showed that prior AEs and a CCI score of 1 (vs 0) in the baseline period increased the likelihood of experiencing an AE after initiating enzalutamide, bicalutamide, or abiraterone therapy, consistent with what has previously been reported among patients with advanced PC 14 .…”
Section: Discussionmentioning
confidence: 73%
“…In ARAMIS trial, authors showed that darolutamide prolonged metastasis-free survival status by 22 months in comparison to the placebo group. Metastasis or death risk was reduced by 59% [64].…”
Section: Efficacy and Safety Study Of Darolutamide (Odm-201) In Men Wmentioning
confidence: 98%
“…Darolutamide is NSAA, which mechanism of action is similar to apalutamide [64]. However, a chemical structure of darolutamide is unique and differs from other AR antagonists by consisting two pharmacologically active diastereomers [84].…”
Section: Darolutamidementioning
confidence: 99%
“…In men with a new diagnosis of high risk (PSADT < 10 months) nonmetastatic castrate resistant prostate cancer (nmCRPC) we recommend consideration of apalutamide, enzalutamide or darolutamide per current standard of care [31][32][33] . In nmCRPC patients with a prolonged PSADT we recommend considering a decrease in the frequency of imaging.…”
Section: Cuaj -Consensus Statementmentioning
confidence: 99%